1996
DOI: 10.1097/00004647-199611000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between High Oxygen Extraction Fraction in the Acute Stage and Final Infarction in Reversible Middle Cerebral Artery Occlusion: An Investigation in Anesthetized Baboons with Positron Emission Tomography

Abstract: Summary: Studies in humans suggest that regions that show maximal increases in brain oxygen extraction fraction (OEF) in the hours following an ischemic episode are those most vul nerable for infarction and are often, although not always, as sociated with the final site of infarction. To clarify this issue, we followed the hemodynamic and metabolic characteristics of regions with an initially maximally increased OEF and com pared them with the ultimately infarcted region in an experi mental stroke model. Posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
70
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(85 citation statements)
references
References 39 publications
(13 reference statements)
15
70
0
Order By: Relevance
“…This has been shown using the permanent MCA occlusion model with PET in baboons with infarct evolution from deep to cortical territory. 13,14 This was similar to our Figure 1 and reflects our observation of higher arterial occlusion rates in classical pattern.…”
Section: Discussionsupporting
confidence: 91%
“…This has been shown using the permanent MCA occlusion model with PET in baboons with infarct evolution from deep to cortical territory. 13,14 This was similar to our Figure 1 and reflects our observation of higher arterial occlusion rates in classical pattern.…”
Section: Discussionsupporting
confidence: 91%
“…Watabe et al (2002) showed that CBF images can be quantitated at much shorter interval than the previous protocol, typically at 90 secs, from sequential PET scanning Altman et al (1991) obtained OEF values of 0.5370.13 from arteriosinus blood sampling. Using steady-state PET, others have measured OEFs ranging from 0.42 to 0.58 in normal tissues of anesthetized monkeys (Altman et al, 1991;Pappata et al, 1993;Touzani et al, 1995;Young et al, 1996;Schumann et al, 1996;Frykholm et al, 2000). Moreover, the values of gCBF in the present PET study were 3079 mL 100/g min from three-step ARG, 3079 mL 100/g min from Previously reported values varied from 27 to 37 mL 100/g min for CBF and 2.4 to 3.4 mL 100/g min for CMRO 2 (Altman et al, 1991;Pappata et al, 1993;Touzani et al, 1995;Young et al, 1996;Schumann et al, 1996;Frykholm et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Using steady-state PET, others have measured OEFs ranging from 0.42 to 0.58 in normal tissues of anesthetized monkeys (Altman et al, 1991;Pappata et al, 1993;Touzani et al, 1995;Young et al, 1996;Schumann et al, 1996;Frykholm et al, 2000). Moreover, the values of gCBF in the present PET study were 3079 mL 100/g min from three-step ARG, 3079 mL 100/g min from Previously reported values varied from 27 to 37 mL 100/g min for CBF and 2.4 to 3.4 mL 100/g min for CMRO 2 (Altman et al, 1991;Pappata et al, 1993;Touzani et al, 1995;Young et al, 1996;Schumann et al, 1996;Frykholm et al, 2000). Variations are because of the differences in monkey species, physiologic conditions, anesthetic agent used, PET scanner, and methodology; the current results clearly show that the DARG method can be used to determine these physiologic parameters with a high degree of accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous perfusion imaging studies using PET, [26][27][28] or CT 9 in animal stroke models have consistently reported CBV decreases in the ischemic area relative to contralateral hemisphere, though with variable degrees of reduction probably reflecting differences in vascular compartments assessed by and spatial resolution of the imaging technique used, MCAo model and timing of measurement as well as species used. Interestingly, a recently published rat study using photoacoustic imaging 32 reported CBV reductions around 70% following branch MCA occlusion, similar to our figure of $80%.…”
Section: Fus Imagingmentioning
confidence: 98%